Study of the Structure of Exotic 52,54,56,58Ca Isotopes Using OXBASH Code - Ali, Akram M.; Khamees, Amenah A. (Iraqi Journal of Science, 2019)
This study dedicates to provide an information of shell model calculations, limited to fp-shell with an accuracy and applicability. The estimations depend on the evaluation of Hamiltoian’s eigenvalues, that’s compatible with positive parity of energy levels up to (10MeV) for most isotopes of Ca, and the Hamiltonian eigenvectors transition strength probability and inelastic electron-nucleus scattering. The Hamiltonian is effective in the regions where we have experimented. The known experimental data of the same were confirmed and proposed a new nuclear level for others.The calculations are done with the help of OXBASH code. The results show good agreement with experimental energy states for 52,54Ca isotopes while a new result are gotten for 56,58Ca isotopes as it is a modern nucleus investigation. For 58Ca , the results are given a smallest 2+ excitation energy with strong B(E2) confirmed by large-“scale shell model in fp-shell space that cannot describe the small energy E(2+) besides that, the reduce transition probability B(E2) in each interaction is different.